تصميم الوظيفة وعلاقته بالالتزام التنظيمي والرضا الوظيفي لدى معلمي ومعلمات محافظنة شمال بسلطنة عمان - Zaabi Laith Khamis Ali
Job design is considered one of factors influencing job satisfaction. It is also considered one of solutions to many organizational commitment obstacles that hinder the level of organizational commitment. Job design is also a factor influencing teachers’ satisfaction. This study aimed at analyzing the degrees of job design and their relation to both organizational commitment and job satisfaction for the teachers of Al Batinah Governorate in the Sultanate of Oman. The researcher used the descriptive correlational approach. The study was conducted on a sample teachers of (n= 329) drawn from the population of (N= 10174). The researcher prepared a questionnaire consisting of (45) valid and reliable factors with were divided into three measures: job design, job satisfaction and organizational commitment. The results of the study showed the moderate mean levels of all job design variables in question. Where by the total means of job design were 3.39, 3.31 for job satisfaction and 3.55 organizational commitment. The results of the regression (R) coefficient=0.518 Sig.=0.000 revealed showed a positive correlation between the degrees of performance, job satisfaction and the level of organizational commitment. Contrariwise, the promotion variables degrees were negatively correlated with the degrees of job satisfaction and organizational commitment. Further results did not show meaningful natural differences among sample statistics by their differences in demographic characteristics. Thus, there were no significant conclusions drawn based on population differences in demographic characteristics. Based on the research findings, the study recommended the establishment of standardized Job design principles so as to enhance job satisfaction and organizational commitment, as well as to arouse the freedom of performance and creativity. It is also recommendable to focus too much on promotion factors for the fear that they may have negative impact on the degree of job satisfaction and organizational commitment among teachers of Al Batinah province in the Sultanate of Oman.